Unusual martensitic strain accommodation mechanism in an electron beam processed metastable β-Ti alloy. (15th January 2023) - Huang, Yuhe; Hernandez-Nava, Everth; Hu, Xiaogang; Todd, Iain; Zhu, Qiang
Abstract: This study reports an unusual martensitic strain accommodation mechanism, in an electron beam processed metastable β-Ti alloy, exhibiting a fine-grained microstructure with good yield strength and elastic modulus matching. Microstructural analysis reveals that ultra-fine laths of martensites were embedded within the fine-grained β structure. Detailed TEM and orientation relationship analyses further unravel that the observed microstructure consists of α'' martensites associated with different habit plane and transformation twins, one with { 7 10 0 }α'' //{755}β type habit plane and forming {111}α'' type I twin while another with {471}α'' //{443}β type habit plane, forming a {351}< 2 ¯ 11 >α'' type II twin. This structure can be interpreted as the product of rapid solidification and thermal stress relaxation which manipulated the formation of distinct martensites that originates from the fluctuated lattice instability, lattice distortion, and transformation strain. This finding provides an alternative route for utilizing the martensitic strain accommodation mechanism, benefiting additive manufacturing β-Ti alloy components with desired mechanical performance. Graphical abstract: Image, graphical abstract